DOCSIS ranging schemes analysis and embedded implementation - WANG Qin; LONG Ping; ZHANG Xiao-tong; LI Zhan-cai (Tongxin xuebao)
First, the MAC ranging schemes based on DOCSIS over bidirectional HFC networks were studied. Then, a calculation method of RTD in bidirectional networks was presented, and an embedded solution of the CM initial ranging schemes was proposed. The solution had been successfully applied to a bidirectional communication platform for HDTV （high-definition television）, which consists of a self-developed PHY ASIC chip and an ARM embedded kernel chip. The experimental results show that the solution could rapidly implement the initial ranging process with high accuracy, and provide good performance and high reliability in various applications.